Analysis of Environmental Conditions in the Andesite Mining Area of Kokap District, Kulon Progo Regency, Yogyakarta, Indonesia: Implications for Environmental Damage Prevention Monitoring - Shilvyanora Aprilia Rande; AA Inung Arie Adnyano; Hendro Purnomo (CV FOUNDAE, 2024)
In this study, an analysis of environmental conditions in andesite mining areas was conducted as a form of monitoring in the prevention of environmental conditions. The methods used in this research are survey, mapping, and analysis methods using scoring that refers to the Decree of Gub. DIY Prop. No. 63 Year 2003. Field observations were conducted to find out information on environmental conditions and determine the areas to be mapped. While mapping is carried out using GPS (Global Position System) tools with medium accuracy of 3-5 meters that are stable. Based on the measurement results seen from the image map, it shows that it has a distance of less than 359.62 meters. The relief of the excavation base with a height tolerance of less than 1 meter, the slope of the excavation cliff with a tolerance reaching an angle of less than 18 degrees, the height of the excavation cliff with a height tolerance of less than 3 meters. The results of data processing and analysis of environmental damage that occurs in andesite stone mining show that the physical environment at the mining site is at a severe level of damage with a total score of 42. The physical environment at the river location is at a moderate level of damage with a total score of 8.